Attenuated post-movement beta rebound associated with schizotypal features in healthy people - Benjamin A.E., Hunt; Elizabeth B., Liddle; Lauren E., Gascoyne; Lorenzo, Magazzini; Bethany C., Routley; Krish D., Singh; Peter G., Morris; Matthew J., Brookes; Peter F., Liddle (Oxford University Press, 2018)
Introduction: Schizophrenia and Schizotypal Personality Disorder (SPD) lie on a single spectrum of mental illness and converging evidence suggests similarities in the etiology of the two conditions. However, schizotypy is a heterogeneous facet of personality in the healthy population and so may be seen as a bridge between health and mental illness. Neural evidence for such a continuity would have implications for the characterization and treatment of schizophrenia. Based on our previous work identifying a relationship between symptomology in Schizophrenia and abnormal movement-induced electrophysiological response (the post-movement beta rebound (PMBR)), we predicted that if subclinical schizotypy arises from similar neural mechanisms to schizophrenia, schizotypy in healthy individuals would be associated with reduced PMBR. Methods: 116 participants completed a visuomotor task whilst their neural activity was recorded by magnetoencephalography. Partial correlations were computed between a measure of PMBR extracted from left primary motor cortex and scores on the Schizotypal Personality Questionnaire (SPQ), a self-report measure of schizotypal personality. Correlations between PMBR and SPQ factor scores measuring Cognitive-Perceptual, Interpersonal and Disorganization dimensions of schizotypy were also computed. Effects of site, age, and sex were controlled for. Results: We found a significant negative correlation between total SPQ score and PMBR. This was most strongly mediated by variance shared between Interpersonal and Disorganization factor scores. Conclusion: These findings indicate a continuum of neural deficit between schizotypy and schizophrenia, with diminution of PMBR, previously reported in schizophrenia, also measurable in individuals with schizotypal features, particularly disorganization and impaired interpersonal relations.